The Relationship between Parenting Patterns and the Incidence of Stunting in Children Aged 25-59 Months - Hermayani, Hermayani; Maran, Peny Wena Betsy (GLOBAL HEALTH SCIENCE GROUP, 2024)
This study examines the relationship between parenting patterns and stunting in children aged 25-59 months in Biak Numfor Regency, where stunting rates surpass the national average. Stunting, a reflection of chronic malnutrition, is particularly high in Papua, highlighting the need for targeted interventions. The research uses a mixed-methods approach, combining quantitative and qualitative data to capture a fuller picture. Designed as a Case Control Study, the research compares mothers of stunted toddlers (46 participants) with mothers of non-stunted toddlers (46 participants), collecting data from January to July 2024 through total sampling. The quantitative phase utilizes secondary data from the Bosnik Public Health Center, while the qualitative phase includes interviews with key health officials. Data analysis involves univariate, bivariate (Chi-Square), and multivariate (Multiple Logistic Regression) methods processed with SPSS 29. Findings show that poor parenting significantly increases the likelihood of stunting by 12.59 times (p=0.001). Additional factors influencing stunting include inadequate prenatal nutrition (AOR 15.43), infrequent prenatal check-ups (AOR 6.026), and a history of premature birth (AOR 5.56). The model predicts an 82.6% incidence rate of stunting based on these risk factors, underscoring the importance of improved maternal and child health practices in the region.